High Education Level Protects European Americans but Not African Americans Against Chronic Obstructive Pulmonary Disease: National Health Interview Survey - Assari, Shervin (Int J Biomed Eng Clin Sci, 2019)
BACKGROUND: Education level reduces the risk of chronic diseases (CDs), including Chronic Obstructive Pulmonary Disease (COPD). Minorities’ Diminished Returns, however, refer to smaller health benefits of socioeconomic position (SEP) improvement for racial and ethnic minorities compared to majority groups. It is not known if MDRs exist for the effects of education level on COPD for African Americans (AAs), relative to European Americans (EAs). AIMS: Using a nationally representative sample, the current study explored racial and ethnic variation in the association between education level and COPD among American adults. METHODS: Data came from the National Health Interview Survey (NHIS 2015), a national survey. A total of 25,488 adults (18+ years old) were included in the study. From this number, 4,533 (17.8%) were AAs and 20,955 (82.2%) were EAs. Education level was the independent variable. Outcome was COPD. Age, gender, and income were the covariates. Race/ethnicity was the moderator. RESULTS: Overall, education level was inversely associated with the odds of COPD. A statistically significant interaction was found between race/ethnicity and education level on odds of COPD, indicating smaller effect of education for AAs compared to EAs. CONCLUSIONS: In line with the Minorities’ Diminished Returns (MDRs), highly educated AAs remained at high risk for COPD, a pattern which is not observed for EAs. Policies that exclusively address racial/ethnic inequalities in SEP may not be enough for eliminating racial/ethnic inequalities in COPD in the US. Public policies must go beyond equalizing SEP and address structural and environmental barriers that disproportionately increase risk of COPD in AAs across SEP levels. Future research should test if residential segregation and exposure to air pollutants contributes to high prevalence of COPD in highly educated AAs. Research is needed on multi-level interventions that may minimize MDR-related health disparities.